Effect Of Some Genetic And Nongenetic Factors On Dry Period In Gir Cows - Rajoriya, Ravi; Tomar, S.S.; Saha, D. N.; Rajoriya, Shweta; Kumar , Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A total of 599 records of dry period on 191 Gir cows maintained at Kasturba Gandhi Memorial Trust, Dairy Farm, Kasturbagram Indore (M.P.) over a period of 36 years from 1974 to 2009 were analyzed by least squares technique using mixed model maximum likely hood computer programme to estimate the effect of sire, period and season of calving, parity and level of inbreeding. The overall least squares means of dry period was estimated to be 158.13±8.56 days. The results indicated that sire (p<0.01), parity (p<0.01) and level of inbreeding (p<0.01) had significant effect on dry period while the effects period of calving and season of calving were non- significant. Inbreeding had deteriorating effect as evidenced by significantly longer dry period in inbred cows as compared to non-inbred cows. Hence proper breeding plan should be evolved to avoid inbreeding in the present herd.